Influence of the length of the internal sleeve valve on the release of powdery substances from the closures of valved bags for dangerous goods. Issue 8 (31st May 2018) - Schlick‐Hasper, Eva; Eiben, Mario; Drousch, Björn; Heinrich, Annika; Goedecke, Thomas; Kraume, Matthias
Abstract : In practice, checks on dangerous goods transports often detect leaks of powdered dangerous goods from valved bags. In this work, the influence factors of a sudden release of powdery substances from the valves of valved bags were investigated. Drop tests were performed on paper bags of UN design type 5M2 with internal sleeve valve using 2 different powdery substances (Esplas H130 and zinc oxide "Rotsiegel"). The internal sleeve valves of all test samples were not sift‐proof with respect to both filling substances. For almost all test samples, the Esplas H130 powder already leaked out of pasted joints during manual filling. This is a contradiction to the requirement in UN 6.1.4.18.1, according to which closures and joints of paper bags 5M2 should be sift‐proof. In the drop tests, longer valve lengths had a greater sealing effect for both filling substances (for filling degrees of at least 95% and for test samples which had already been mechanically loaded). As an extreme example, at the drop height of 1.20 m and a filling degree of 100%, the released amount of zinc oxide powder from a 10‐cm‐long valve was about 16 times higher than from a valve length of 12.5 cm. The valve length is therefore a safety‐relevant parameter and should be specified by the manufacturer. To ensure that only filling goods with similar physical properties in comparison with the test substance are used for valved bags, the user must be informed of the particle size of the test substance. Abstract : Fourier transform infrared spectroscopy combined with principal component analysis (PCA) after first derivative pretreatment was used to discriminate virgin and recycled expanded polystyrene (EPS) food containers. The degradation occurring in the recycling process would lead to an increase of the absorbance in carbonyl region (1780‐1620 cm −1 ), which could serve as variables for building PCA model.